2020
DOI: 10.1128/aac.02167-19
|View full text |Cite
|
Sign up to set email alerts
|

Fact versus Fiction: a Review of the Evidence behind Alcohol and Antibiotic Interactions

Abstract: Many antibiotics carry caution stickers that warn against alcohol consumption. Data regarding concurrent use are sparse. An awareness of data that address this common clinical scenario is important so health care professionals can make informed clinical decisions and address questions in an evidence-based manner. The purpose of this systematic review was to determine the evidence behind alcohol warnings issued for many common antimicrobials. The search was conducted from inception of each database to 2018 usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Unfortunately, the limited number of studies did not allow us to draw any definitive conclusion. interactions between alcohol and these medications is sparse and often discordant (Mergenhagen et al, 2020). In our study, we found that among participants taking some antibiotics (e.g., penicillins, amoxicillin, doxycycline), those who consumed alcohol differed from those who consumed placebo in some PK values.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 61%
“…Unfortunately, the limited number of studies did not allow us to draw any definitive conclusion. interactions between alcohol and these medications is sparse and often discordant (Mergenhagen et al, 2020). In our study, we found that among participants taking some antibiotics (e.g., penicillins, amoxicillin, doxycycline), those who consumed alcohol differed from those who consumed placebo in some PK values.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 61%
“…However, it is not uncommon that some Vietnamese people to have a habit of drinking large amounts of alcohol, and being drunk may affect treatment adherence. In particular, when treated with regimens containing metronidazole or tinidazole, patients who drank alcohol during the treatment period are prone to severe side effects such as nausea, vomiting, headache, and flushing ( 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, despite all of these promising results, it must be said that hydrogen cyanamide is poisonous for humans—it can produce a disulfiram-like syndrome, in which acetaldehyde accumulates in the blood, producing headaches, low blood pressure, palpitations, nausea, and chest pain ( Mergenhagen et al, 2020 ). Its use has therefore been banned in many countries worldwide ( Sheshadri et al, 2011 ), including European Union countries, New Zealand, and more.…”
Section: Effects Of Agrochemicals On Endodormancy Releasementioning
confidence: 99%